«Love for the fatherland created our state»: I. E. Zabelin on historical knowledge (based on archival materials) - Kokorina, Julia G. (Journal of the Belarusian State University. History, 2025)
The outstanding Russian historian I. E. Zabelin is known for his research on the history of pre-Petrine Russia and ancient Moscow, as well as his archaeological excavations in the Northern Black Sea region. The scholar’s contemporaries had mixed feelings about his ideas on the nature of historical science, although the prevailing opinion was positive. During the Soviet era, I. E. Zabelin was considered a monarchist historian, and his scientific works were often treated with contempt. The post-Soviet era has been characterised by attempts to take an objective view of the scholar’s theoretical legacy. An analysis of his reflections on the essence of historical knowledge seems particularly relevant at the present time of crisis and change, when humanity is turning to the past in search of answers to pressing questions. In this regard, I. E. Zabelin’s manuscript legacy is being studied in the context of the development of historical thought in his era, and the historian’s notes, which are stored in his archive, are being introduced into scientific circulation for the first time and compared with his printed works of a programmatic nature. The uniqueness of the researcher’s views on historical knowledge is revealed. He links history with moral categories, comments on the essence of the vigilante system based on comradeship, and considers historical facts to be the bearers of ideals. I. E. Zabelin opposes the mindless «collection» of facts and sees the need to reveal the patterns of the historical process. For him, history is a search for freedom. The researcher views history as a science about society, rather than about the exploits of individuals or unique events. In his opinion, the task of historical knowledge is to shape the personality in society, and the task of the state as a historical phenomenon is to serve the individual and the people, which is why Moscow rose to prominence as the centre of the Russian lands. I. E. Zabelin believes that love for the fatherland was the reason for the creation of the Russian state.